SAT0529 Impact of Pre-Treatment Renal Insufficiency on Renal Cortical Atrophy After Corticosteroid Therapy in IgG4-Related Kidney Disease: A Retrospective Multicenter Study. (9th June 2015) - Mizushima, I.; Yamamoto, M.; Inoue, D.; Yamada, K.; Ubara, Y.; Matsui, S.; Nakashima, H.; Nishi, S.; Kawano, M.
Abstract : Background: IgG4-related disease (IgG4-RD) is a recently recognized systemic inflammatory disorder that can affect many organs [1]. It frequently causes various renal lesions, which are collectively referred to as IgG4-related kidney disease (IgG4-RKD) [2]. In this disease, focal or diffuse renal cortical atrophy is often observed in the clinical course after corticosteroid (CS) therapy [3]. However, the factors related to such renal atrophy have not been well clarified. Objectives: To clarify the factors related to renal atrophy after CS therapy in IgG4-RKD. Methods: We retrospectively evaluated clinical features including laboratory data, computed tomography (CT) findings before and after CS therapy in 22 patients diagnosed with IgG4-RKD based on the diagnostic criteria for IgG4-RKD [2], all of whom were followed up for more than 20 months. Results: Sixteen patients were men, and six were women (average age 61.5 years). Average follow-up period was 52.4 months (range 20-93). At diagnosis, their serum IgG4 level was 1043±531 mg/dL, and 7 patients showed hypocomplementemia. The average estimated glomerular filtration rate (eGFR) was 67.9 mL/min/1.73m 2 . All patients had extra-renal organ involvement. Multiple low-density lesions (LDLs) on contrast-enhanced CT were observed before CS therapy in all patients. All patients were treated with prednisolone (PSL) at an average initial dose of 35.5±8.4 mg/day (range 20-50), and showed disappearance or reduction of LDLs. At least a part of LDLs resulted in partial renal cortical atrophy in 13 patients (Group A), whereas complete recovery with normal contrast enhancement without a residual cortical scar was achieved in 9 patients (Group B). Pre-treatment eGFR in Group A was significantly lower than that in Group B (60.2±23.4 mL/min/1.73m 2 vs 79.0±19.4 mL/min/1.73m 2, P =0.035), and the percentage of patients with less than 70 mL/min/1.73m 2 of eGFR in Group A was significantly higher than that in Group B (69.2% vs 22.2%, P =0.040). None of the other factors including age, gender, number of involved organs, serum IgG4 and complement levels, initial dose of PSL, renal function after therapy, recurrence rate of renal lesions, prevalence of diabetes mellitus or hypertension, and follow-up period significantly differed between the two groups. Conclusions: The present study suggests that pre-treatment renal insufficiency may relate to renal atrophy after CS therapy in IgG4-RKD. Whether an early initiation of therapy before renal function declines would prevent the development of renal atrophy remains to be clarified through a larger-scale prospective study. References: Stone JH et al. IgG4-related disease. N Engl J Med. 2012 Feb 9;366(6):539-51. Kawano M et al. Proposal for diagnostic criteria for IgG4-related kidney disease. Clin Exp Nephrol. 2011 Oct;15(5):615-26. Saeki T et al. The clinical course of patients with IgG4-related kidney disease. Kidney Int. 2013 Oct;84(4):826-33. Disclosure of Interest: None declared